Alignment mechanisms for supplier-initiated innovation: Results from the logistics service industry. Issue 5 (December 2019) - Wallenburg, Carl Marcus; Johne, Dennis; Cichosz, Marzenna; Goldsby, Thomas J.; Knemeyer, A. Michael
Abstract: In service outsourcing, buying organizations frequently experience shortcomings in supplier-initiated innovation. To address this problem, we develop a model that distinguishes two mechanisms for buyer-supplier alignment (i.e. relational and formal innovation alignment) and outlines how their effectiveness differs depending on the level of hierarchy in the relationship. Using data from the logistics service industry, it is shown that when the level of hierarchy is comparatively low, where buyers and suppliers interact participatively, both relational and formal innovation alignment are effective in fostering supplier-initiated innovation. Yet, as the relationship becomes more hierarchical and dominated by the buyer, the effect of relational innovation alignment diminishes and eventually turns negative, while the effect of formal innovation alignment is strengthened. Highlights: Formal and relational inovation alignment between buyer and supplier facilitate innovation in service outsourcing. Hierarchical and non-hierachical buyer-supplier relationships show very different relationship dynamics. The effect of innovation alignment on supplier-innitiated innovation is contingent upon the relationship context.